Direct WIMP detection with cryogenic detectors. - Kraus, H (2003)
Cryogenic detectors have been developed since the mid 1980s and have been applied successfully to dark-matter searches since the mid 1990s. Among the advantages of cryogenic detectors are their high sensitivity to nuclear recoil, their low detection thresholds, the wide choice of target materials and the possibility of implementing event type recognition on an event-by-event basis. I explain the basics of cryogenic detectors, review various implementations, discuss advantages and drawbacks and give an overview of current dark-matter-search experiments based upon cryogenic detectors.